SISTEM INFORMASI PEMASARAN HASIL KERAJINAN ANYAMAN GELAS RUMAH TANGGA - Muh. Rasyid Ridha; Mahdalina (JURNAL PERANGKAT LUNAK, 2019)
Marketing is something that contains all systems related to the purpose of determining prices up to approval and cmpletting goods and services that can meet actual and potencial buyers needs. The more creative the marketing will be more and consumers are intersted. One form of creative marketing by using a web based information system with a unique and attractive appearance. Currently, the development of the internet is also very fast, either in person or agency is in need of internet. They use the internet to present the latest information services required by the community. An agency or company is in need of internet services. As in Ranbow desa Sungai Dusun, they desperately need promotion services to market the production is widespread, but during this promotion are still using manual system only. Web based marketing information system using PHP progamming language designed using Dreamweaver 8 applcation and the MYSQL database.